Roll and pitch of the rider's pelvis during horseback riding at walk on a circle - Egenvall, A.; Clayton, H.; Engell, M. T.; Roepstorff, C.; Engström, H.; Byström, A. (Journal of Equine Veterinary Science, 2022)
The study investigated between-rider differences in pelvic roll and pitch motion during horseback riding as the horse walked around circles without rein contact (walk on long reins), with rein contact, and with moderate collection. Ten horses were ridden by five riders on left and right 10 m circles, in a partly crossed design, yielding 14 trials. Each trial included each of the three walk variations in both directions. Riders wore an inertial measurement unit (IMU), logging at 100 Hz, dorsally on the pelvis. Pelvic roll and pitch data were split into strides based on data from IMU-sensors on the horse's hind cannons. Data were analyzed using signal decomposition into the fundamental frequency (the stride frequency) and its first two harmonics. Mixed models accounting for the type of walk were used to analyze how riders differed in roll and pitch pelvic motion in two ways: comparing amplitudes of the frequency components and comparing whole stride mean data. Graphically pelvic pitch showed substantial timing and amplitude differences between riders, and this was confirmed statistically. Pelvic roll timing was similar, but amplitude varied between the riders, both graphically and statistically. Individual rider patterns tended to persist across different horses and all exercises. These results suggest that exercises at walk can be ridden with different pelvis pitch timing, a fact that has so far not been discussed in the equestrian literature. Whether pelvic pitch timing affects the horse's performance remains to be investigated.